2018
DOI: 10.20884/1.sar.2018.3.1.1158
|View full text |Cite
|
Sign up to set email alerts
|

Some Factors That Affect Transfer Pricing Decision

Abstract: The objectives of this research is to analyze the effect of tax minimization, firm size, foreign ownership bonus mechanism, and exchange rate on transfer pricing decision in multinational company engaged in manufacturing that listed on Indonesia Stock Exchange from the year of 2015 to 2016. Sampling method in this study is using purposive sampling using 8 criterias that have been determined. The result of binary regression analysis shows that only tax minimization that has positive effect on transfer pricing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 17 publications
1
8
0
5
Order By: Relevance
“…Foreign operations measured by foreign share ownership do not impact the future transfer pricing scale for transactions that trigger debts with related parties abroad. The findings are supported by Septiyani et al (2018), which shows no relationship between foreign ownership and transfer pricing exists because the sample does not consider the proportion of particular relation transactions outside foreign ownership. The relationship between families, which can cause transactions between associated parties, is another thing to be considered.…”
Section: The Influence Of Foreign Operations On Transfer Pricingmentioning
confidence: 77%
See 1 more Smart Citation
“…Foreign operations measured by foreign share ownership do not impact the future transfer pricing scale for transactions that trigger debts with related parties abroad. The findings are supported by Septiyani et al (2018), which shows no relationship between foreign ownership and transfer pricing exists because the sample does not consider the proportion of particular relation transactions outside foreign ownership. The relationship between families, which can cause transactions between associated parties, is another thing to be considered.…”
Section: The Influence Of Foreign Operations On Transfer Pricingmentioning
confidence: 77%
“…The larger the shareholding of foreign controlling shareholders, the greater their power in deciding the company's decisions. Septiyani et al (2018) reported that foreign controlling shareholders could sell products from companies they own to other privatelyowned companies at prices below market prices. The transfer pricing can be evaluated through related party transactions of assets and liabilities (RPTAL) and transfer pricing intensity (TPI).…”
Section: H3mentioning
confidence: 99%
“…Hasil sebaliknya ditunjukkan oleh Yulianti dan Rachmawati (2019) yang menyatakan bahwa debt covenat berpengaruh negatif tidak signifikan terhadap transfer pricing. Penelitian Alino dan Lane (2015), Septiyani et al, (2018), Refgia et al, (2017), dan Noviastika et al, (2016, menunjukkan bahwa tax minimization berpengaruh positif signifikan terhadap transfer pricing. Sementara itu, Merle et al, (2019) serta Susanti & Firmansyah (2018) menyatakan tax minimization berpengaruh negatif dan signifikan terhadap transfer pricing.…”
Section: Pendahuluanunclassified
“…Hartati et al, (2015) mengartikan tax minimization sebagai suatu strategi untuk meminimalkan beban pajak terutang melalui tindakan transfer biaya dan pada akhirnya transfer pendapatan ke negara dengan tarif pajak yang rendah. Jacob (1996) dalam penelitian Septiyani et al, (2018) menemukan bahwa transfer antara perusahaan besar dapat menyebabkan pembayaran pajak global yang lebih rendah secara umum. Pada penelitian ini, penulis menggunakan proksi Effective tax rate (ETR) untuk mengukur tax minimization.…”
Section: Debt Covenantunclassified
See 1 more Smart Citation